2012
DOI: 10.1016/j.neuron.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Is Required for Learning and Forgetting in Drosophila

Abstract: SUMMARY Psychological studies in humans and behavioral studies of model organisms suggest that forgetting is a common and biologically regulated process, but the molecular, cellular, and circuit mechanisms underlying forgetting are poorly understood. Here we show that the bidirectional modulation of a small subset of dopamine neurons (DANs) after olfactory learning regulates the rate of forgetting of both punishing (aversive) and rewarding (appetitive) memories. Two of these DANs, MP1 and MV1, exhibit synchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
300
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(336 citation statements)
references
References 47 publications
21
300
1
2
Order By: Relevance
“…We anticipated that hits affecting acquisition might alter the processing of the CS signal, the unconditioned stimulus (US) signal, or the integration of the CS and US. Hits that alter memory stability may alter general mechanisms that promote memory stabilization that are not yet well defined, consolidation of memories into a form resistance to experimental insults, or forgetting (Dudai et al 1976;Tully et al 1994;Shuai et al 2010;Berry et al 2012). Within the first few hours after conditioning, Drosophila olfactory memories are known to consist of anesthesia sensitive memory (ASM), a form disruptable with cold anesthesia, and anesthesia resistant memory (ARM), a consolidated form of memory that is resistant to this treatment (Folkers et al 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipated that hits affecting acquisition might alter the processing of the CS signal, the unconditioned stimulus (US) signal, or the integration of the CS and US. Hits that alter memory stability may alter general mechanisms that promote memory stabilization that are not yet well defined, consolidation of memories into a form resistance to experimental insults, or forgetting (Dudai et al 1976;Tully et al 1994;Shuai et al 2010;Berry et al 2012). Within the first few hours after conditioning, Drosophila olfactory memories are known to consist of anesthesia sensitive memory (ASM), a form disruptable with cold anesthesia, and anesthesia resistant memory (ARM), a consolidated form of memory that is resistant to this treatment (Folkers et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The combined data suggest that sickie knockdown has no effect on the acquisition of information, but is involved in subsequent memory stability. Since dopaminergic neurons have been proposed to chronically release dopamine after learning to promote forgetting (Berry et al 2012), an attractive working hypothesis is that sickie RNAi reduces the dopaminergic forgetting signal.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study we found that 20-E treatment enhances the expression of the dopamine receptor gene, Amdop2, in the mushroom bodies of the brain. Interestingly, the Drosophila ortholog of this gene, DAMB, which is highly expressed in the mushroom bodies of the fly (Han et al 1996), has recently been implicated in forgetting (Berry et al 2012). However, dopamine signaling, at least in flies, is involved not only in aversive learning, but also in the formation of appetitive olfactory memories (Kim et al 2007;Selcho et al 2009;Burke et al 2012;Liu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons from the ventral tegmental area also participate in a circuit, which controls the mammalian sleep-wake cycle. In flies, these pathways have been dissected to yield a detailed understanding of input/output-relation, decision-making and memory formation [18,21,22,[69][70][71][72][73][74][75]: dopaminergic input impinges on the mushroom body output neurons: PPL1 dopaminergic neurons are involved in aversive olfactory reinforcement [76,77]. PAM dopaminergic neurons promote reward reinforcement [22,71,72,78].…”
Section: The Dopaminergic Systemmentioning
confidence: 99%
“…The signaling pathways underlying memory formation and extinction have also been addressed in two dopaminergic neurons residing in PPL1 (MP1 and MV1), which show synchronized ongoing activity before and after learning. Memory acquisition and extinction, depend on Dop1R1 (or dDA1) and Dop1R2 (or DAMB), respectively [70]. In addition to coupling with Gs, Dop1R2 also signals via Gq, which mediates the extinction of memory [79].…”
Section: The Dopaminergic Systemmentioning
confidence: 99%